As maneiras de combate na Lusitánia - Canosa, José Angel Fernández (Trabalhos de Antropologia e Etnologia, 2020)
The bands of warriors of Lusitania, as much as Viriato's warriors, whkh were studied from the evidence left by the Greek-Latin historiography and beyond its diche's, were professional warriors lilm those characterizing many of the ancient societies. The type of activities used in combat, resemble the typical warrior of the Indo-European worlcl, with whom they are, of course, identified through common fighting methods.